Anodic oxidation of synthetic refinery effluent on lead anode: mass transport and charge rate balance - T. Zier (IWA Publishing, 2021)
A synthetic wastewater based on Algiers refinery real effluent was prepared and treated using anodic oxidation. Full factorial plan design was used to conduct the statistical analysis of the results. The aim of the study was to assess the interaction between current density (CD) and stirring degree (SD), and quantify their effects on chemical oxygen demand (COD) removal and electric energy specific consumption (EESC). With an initial COD of 487 mg/L, pH of 5.5 and 0.05 M of Na2SO4 as supporting electrolyte, it was found that a 55 rpm stirring degree variation led to a substantial gain in COD removal and energy consumption: 6% and 8.5 KWh/kg, respectively. Current density was found to have a different effect on removal efficiency within the applied stirring domain, and mass transport coefficient (km) is inversely correlated to energy consumption. A theoretical model describing the process was reviewed and the relation between concentration, hydrodynamics and applied current was emphasized. HIGHLIGHTS A simple empirical modeling to assess charge rate and mass transport rate balance (i.e. operating regime).; Lead anode was first applied for electro-oxidation of toluene.; Perspectives on the up-scaling approach taken and comparative data were discussed.; Theoretical modeling review.;